An experimental evaluation on expressivity and efficiency of vertex-centric graph processing paradigm - Liu, Siyuan (2018)
Distributed graph processing has gained popularity in recent years. Among var- ious graph processing models, the vertex-centric model is implemented in many graph processing systems. Many optimization techniques have been proposed and extensive empirical evaluation has been done for various systems. However, no previous work has evaluated the vertex-centric model itself. In this final year project, the expressivity and efficiency of the model itself are studied with con- crete graph problems and datasets. Experimental results demonstrate that the model has limited expressivity and suffers from inefficiency.